Analysis of reasons for discarding of blood and blood products in a tertiary care hospital - Dr. Vimal Mourouguessine; Rakesh Balla; Dr. Nishanthi Anandabaskar (Tropical Journal of Pathology and Microbiology, 2019)
Introduction: A quality management system should be followed at all stages of collection, processing, storing and issuing of blood products. Hence it is vital to know the discarding of blood products at the blood banks to improve the transfusion services and for effective management of the blood products. Aim: To find the various reasons for discarding of blood products and to explore the strategies to minimize its wastage in the blood bank of a tertiary care hospital. Materials and methods: Data was collected from the master blood donor register, whole blood and components record and discarding register for a period of three years. The information on total blood products prepared, total number of products discarded and the reason for discarding was retrieved from these records. Results: In the study period, expiry was the main reason for discarding of whole blood and platelets. Packed cells were discarded due to expiry, Transfusion transmissible infections and damaged bag. Damaging due to the handling was the common reason for discarding of FFPs and none of the Cryoprecipitate was discarded. Hepatitis B infection was the most common cause of Transfusion transmissible infection followed by Syphilis in the present study. Conclusion: Meticulous screening of donors prior to blood donation, sensitizing the clinicians on rational use of blood products, training of blood bank personnel and practicing standard transfusion protocols will minimize the discard rate of blood and blood products in the blood banks.